Synthesis, Experimental and Computational Evaluation of SERAAK1 as a 5-HT2A Receptor Ligand - Agata Zięba; Ewa Kędzierska; Michał K. Jastrzębski; Tadeusz Karcz; Agnieszka Olejarz-Maciej; Agata Sumara; Tuomo Laitinen; Tomasz M. Wróbel; Emilia Fornal; Marián Castro; Agnieszka A. Kaczor (Molecules)
Many drug discovery efforts have identified potentially promising molecules; however, a common limitation of these reports is the lack of further experimental confirmation of pharmacokinetic properties and behavioral effects of discovered compounds. In this study, we aim to address this limitation. Therefore, we build on our previous virtual screening campaign by synthesizing, analyzing in silico, and evaluating experimentally the SERAAK1 compound, which was initially identified as a ligand for 5-HT1A, 5-HT2A, and D2 receptors. Through these investigations, we discovered that SERAAK1 binds to the orthosteric pocket of the 5-HT2A receptor in a similar mechanism to that known for marketed antipsychotic medications. Molecular dynamics simulations revealed that the SERAAK1 compound remains stable in the orthosteric binding pocket of the 5-HT2A receptor. The determination of the ADMET parameters indicated the directions for further optimization of the compounds. In vivo studies demonstrated the anxiolytic and antidepressant properties of the SERAAK1 compound.